Optimalisasi Ukuran Unit Tipe 36 terhadap Kepuasan Penghuni Rumah Susun (Studi Kasus: Rumah Susun Asn Pasar Jumat) - Hartono, Mochamad; Rilatupa, James E.D; Martowardjojo, Aryantono (Green Publisher Indonesia, 2025)
This study aims to evaluates the suitability of Type 36 unit sizes in meeting resident satisfaction at the ASN Pasar Jumat Flat and proposes design optimization strategies to improve quality of life. Space optimization is defined as maximizing room functionality through efficient layouts, multifunctional furniture, and improvements in elements such as ventilation and lighting, without altering the main structure. Resident satisfaction is measured based on perceptions of comfort, mobility space, storage capacity, privacy, and environmental health, assessed through standardized questionnaires. The study employs a qualitative approach, focusing on in-depth interviews to understand residents’ experiences with Type 36 units. Open-ended questionnaires complement the interviews to identify satisfaction themes, while physical measurements verify reported spatial conditions. Data from these three methods are thematically analyzed to generate deep insights into design optimization. Findings indicate that Type 36 units fall short of residents’ expectations in terms of mobility space, storage, and ventilation. Layout, natural lighting, and privacy are also hindered by dimensional constraints. The study proposes design optimization through spatial reconfiguration, the use of foldable or built-in furniture, and improvements in ventilation and lighting. The research provides practical recommendations for managers and policymakers, including adaptive design guidelines and phased renovations, to enhance flat housing standards for ASN, particularly at the ASN Pasar Jumat Flat, and as a reference for future flat developments.